2020
DOI: 10.21203/rs.3.rs-122465/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MiR-191-5p Is Upregulated in Culture Media of Implanted Human Embryo on Day Three of Development

Abstract: Background: Morphologic features are the most common criteria for selecting human embryo to be transferred to the receptive uterine cavity. However, such characteristics are not valid for embryos in cellular arrest. The aim of this study was to quantify the expression profile of hsa-miR-21-3p, -24-1-5p, -191-5p, and -372-5p on day 3 of culture media from in vitro fertilization (IVF) embryo that were implanted or failed to be implanted in patients (n=25 pregnant and 25, non-pregnant patients). Methods: Fifty pa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Nevertheless, it is worth noting that this difference did not reach statistical signi cance. In a separate study by Acua-González et al [13], miR-191-5p was found to be signi cantly elevated in the culture media of blastocysts that successfully implanted at day 5. Conversely, Rosenbluth et al [9] reported higher expression of miR-191 in the blastocyst culture medium of aneuploid embryos and embryos that failed to implant.…”
Section: Discussionmentioning
confidence: 88%
“…Nevertheless, it is worth noting that this difference did not reach statistical signi cance. In a separate study by Acua-González et al [13], miR-191-5p was found to be signi cantly elevated in the culture media of blastocysts that successfully implanted at day 5. Conversely, Rosenbluth et al [9] reported higher expression of miR-191 in the blastocyst culture medium of aneuploid embryos and embryos that failed to implant.…”
Section: Discussionmentioning
confidence: 88%